Interleukin-15 and soluble interleukin-15 receptor α in coronary artery disease patients: association with epicardial fat and indices of adipose tissue distribution. - Elena Dozio; Alexis Elias Malavazos; Elena Vianello; Silvia Briganti; Giada Dogliotti; Francesco Bandera; Francesca Giacomazzi; Serenella Castelvecchio; Lorenzo Menicanti; Alexander Sigrüener; Gerd Schmitz; Massimiliano Marco Corsi Romanelli (PLoS ONE, 2014)
Interleukin-15 (IL-15) is a pro-inflammatory cytokine which signals via a specific alpha receptor subunit (IL-15Rα). Increased IL-15 level has been observed in cardiovascular patients and IL-15 immunoreactivity has been detected at vulnerable atherosclerotic plaques. Due to the association between adipose tissue distribution, inflammation and coronary artery disease (CAD), we quantified IL-15 and IL-15Rα in CAD patients with different adiposity and adipose tissue distribution and we evaluated whether epicardial adipose tissue (EAT), a visceral fat depot surrounding and infiltrating myocardium, may be a source of both molecules. IL-15 and IL-15Rα proteins were quantified by enzyme-linked immunosorbent assays. Gene expression of IL-15 and IL-15Rα in EAT depots was evaluated by one colour microarray platform. EAT thickness was measured by echocardiography. Plasmatic IL-15 and IL-15Rα levels were higher in CAD than non-CAD patients. After classification according to adipose tissue distribution, IL-15 was higher in CAD patients with increased abdominal adiposity. Increased level of IL-15Rα was observed both in CAD and non-CAD patients with increased abdominal fat. EAT was a source of IL-15 and IL-15Rα and their expression was higher in CAD patients with increased EAT thickness. In conclusion, our data suggest that circulating levels of IL-15 and IL-15Rα seem to reflect visceral distribution of adipose tissue and that EAT may be a potential source of both IL-15 and IL-15Rα. Future studies on the relationship between IL-15, visceral fat and characteristics of atherosclerotic plaques could help to better understand the complex biology of this cytokine.